2016
DOI: 10.1155/2016/6539858
|View full text |Cite
|
Sign up to set email alerts
|

Static Balance in Patients with Vestibular Impairments: A Preliminary Study

Abstract: Aims. Vestibular system is indicated as one of the most important sensors responsible for static and dynamic postural control. In this study, we evaluated static balance in patients with unilateral vestibular impairments. Materials and Methods. We compared static balance control using Kistler force plate platform between 10 patients with unilateral vestibular impairments and 20 normal counterparts in the same sex ratio and age limits (50 ± 7). We evaluated excursion and velocity of center of pressure (COP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Studies have shown that patients with vestibular disorders have increased COP sway path lengths and mean velocities [ 21 ] and that nGVS can enhance the function of vestibular afferents [ 22 ]. These findings suggest that the improved function of vestibular afferents may have reduced COP sway observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with vestibular disorders have increased COP sway path lengths and mean velocities [ 21 ] and that nGVS can enhance the function of vestibular afferents [ 22 ]. These findings suggest that the improved function of vestibular afferents may have reduced COP sway observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The control of standing balance requires sensory inputs from the visual, somatosensory and vestibular systems and appropriate motor commands to the musculoskeletal system [2,4,35,44]. Vestibular disorders can disrupt sensory control of posture [36] as well as vestibular reflexes involving postural muscle responses [1], leading to balance problems and increased risk of falls [16,28,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…During this period of time, patients might have altered their balance performance because of the vestibular disorders, which might increase the risk of falling [30]. There have been studies investigating balance performance in people with vestibular disorders [12,44]. There was evidence showing that balance performance of BPPV patients could be effectively ameliorated by a canalith repositioning manoeuver [5,11,13,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Balance is the ability to maintain a stable body position in various positions when moving under the influence of external forces [14]. The balance is of two types: static balance that is the ability to maintain the body position stationary, in the stable position [38], and dynamic balance that is the body posture maintenance in changing body positions while making movements and their combinations [24]. The static and dynamic balance is not very closely related to each other with a good static balance, a person may have difficulties when performing the tasks of dynamic balance [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of factors, influencing the balance: vestibular apparatus, information from external and internal receptors, functionality of the central nervous system, age, changes of the body mass center, emotional state, muscle strength, muscle activation, coordination, flexibility, level of training, motor development, genetics, and gender [1,14,20,34,38,42]. Good balance depends on the accepted signals to the central nervous system (CNS) from visual, vestibular, and proprioceptive systems [37].…”
Section: Introductionmentioning
confidence: 99%